Understanding Cooperation in an Intertemporal Context - Felix Kölle; Thomas Lauer (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
In today's highly complex economic environment, cooperation among individuals is crucial for organizational and societal success. Most of the situations in which cooperation is required involve costly efforts whose consequences play out over time. Here, we provide a systematic and comprehensive analysis of cooperation in an intertemporal context. In a first study, we show that cooperation is substantially reduced when the benefits of cooperation are shifted towards the future, and increased when the costs are delayed. An analysis of the underlying behavioral mechanisms reveals that the change in cooperation can be explained by (i) a shift in the beliefs about others' actions, (ii) a shift in the willingness to conditionally cooperate, and (iii) an individual's degree of impatience. We further demonstrate that social norms are unaffected by the timing of consequences, indicating that the shifts in conditional cooperation are due to a change in norm compliance rather than the norm itself. In a second study, we demonstrate that the amount of economic incentives needed to close the cooperation gap are substantial, thereby providing policy makers with a useful estimate for conducting cost-benefit analyses.
Keywords: H41; D63; C92; 330; Cooperation; time preferences; incentives; social norms; experiment